On the relationship between innovation and performance: A sensitivity analysis - Hans Lööf; Almas Heshmati (Stockholm School of Economics, The Economic Research Institute (EFI), 2001)
The objective of this study is to investigate the sensitivity of the estimated relationship between innovation and firm performance. In doing so, we rely on a knowledge production function approach and carry out comparisons in a number of respects. The sensitivity analysis is based on the comparison of a basic econometric model with different alternative models using the same data sources, an identical model but different data sources, different classifications of firm performance and different classifications of innovation. The analyses are performed in both level and growth rate dimensions. The overall picture gives indications of what factors cause variations in the estimated effects of interest and the direction of changes.
Keywords: C24; C31; L60; O31; O32; 330; Knowledge capital; productivity; innovation; manufacturing; services; knowledge intensity; Community Innovation Survey